(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The article aims to bring the issue of 41 bis “down to earth”, reconstructing its origins and meaning. It analyzes the historical relationship between the mafia and prison, and more broadly between the mafia, prison, and the state. It then offers an exemplary and concrete representation of the influence of this relationship on the history of the fortunes of the great mafia organizations. Finally, he goes back to August 1992, when the law was approved in parliament, to recall the climate in which it was approved and the - still valid - project that animated it.